2017
DOI: 10.3389/fonc.2017.00008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PET/MRI for Tumor Volume Delineation for Head and Neck Cancer

Abstract: IntroductionComputed tomography (CT), combined positron emitted tomography and CT (PET/CT), and magnetic resonance imaging (MRI) are commonly used in head and neck radiation planning. Hybrid PET/MRI has garnered attention for potential added value in cancer staging and treatment planning. Herein, we compare PET/MRI vs. planning CT for head and neck cancer gross tumor volume (GTV) delineation.Material and methodsWe prospectively enrolled patients with head and neck cancer treated with definitive chemoradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…Because of this, 18 F-FDG PET is combined with morphological imaging methods, like CT or MRI [3]. Magnetic resonance imaging has a potential advantage over CT, since it is characterized by excellent soft tissue contrast, which allows for detection of infiltration of adjacent structures or perineural and vascular spread [7]. The prospective study by Lonneux et al.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, 18 F-FDG PET is combined with morphological imaging methods, like CT or MRI [3]. Magnetic resonance imaging has a potential advantage over CT, since it is characterized by excellent soft tissue contrast, which allows for detection of infiltration of adjacent structures or perineural and vascular spread [7]. The prospective study by Lonneux et al.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of combined PET/MRI into RT, however, requires patient examination in RT position for accurate image alignment with the RT planning CT [6] , [24] , [25] , [26] , [27] . Especially for HNC, it has been shown that the accuracy of rigid or deformable registration algorithms is strongly improved when patient images are acquired in RT position for both CT and MRI [26] , [27] .…”
mentioning
confidence: 99%
“…In addition, spatial analysis within GTV-MRI, GTV-PET and GTV-PET/MRI was performed. The Dice similarity coe cient (DSC) was calculated using the equation: 2 × (A∩B)/(A + B), where A and B represent two volumes, (A∩B) represents the volume of the intersection, and (A + B) represents the absolute sum of their volumes [11].…”
Section: Resultsmentioning
confidence: 99%
“…In their study, GTV VIS and GTV FUS were larger than GTV MRI with the use of hybrid PET/MRI images, which was similar to our ndings, but tumor site determinations were different. While Wang, K. et al [11] demonstrated that hybrid PET/MRI-and CT-generated GTVs were similar overall and supplied similar radiation doses to the head and neck. Zhang, Shaomin.…”
Section: Discussionmentioning
confidence: 99%